Revisiting Men of Maize: Historical Truths, Literary Distortions, and Asturias in Today’s Guatemala - Elaine Elliott (Maya America)
In 2024, a renewed appreciation for the Guatemalan Nobel Prize winner Miguel Ángel Asturias is taking place to mark the 50th anniversary of Asturias’ death. This essay examines the historical and literary context of the author’s groundbreaking novel Hombres de maíz (Men of Maize), and the book’s portrayal of indigenous Maya resistance against ladino landowners in Guatemala. Evidence indicates that Asturias obtained his views of ladino – Maya conflict from historic land conflicts in Ilom, Chajul. Asturias distorted the events, but his book inspired a generation of revolutionaries, some of whom organized and fought in the Ixil region and Ilom. The novel’s protagonist, Gaspar Ilom, took on a new life when Asturias’ son (Rodrigo) became a revolutionary and adopted the name “Gaspar Ilom” as his nom de guerre. In the post-revolutionary period, Guatemalan Maya, including Ixil Maya, advocated for human rights on a national and international stage. Today, Maya intellectuals critique Men of Maize for unethically distorting their culture and reality, but some Maya will recognize the book’s literary merits and potential for worthy discussion.